1844 R.I. Pub. Laws 503 § 1 - (:unkn) unknown (General Publisher, 1844)
Required all white males aged eighteen to forty-five years old to be enrolled in the militia except idiots, lunatics, common drunkards, paupers, vagabonds, and persons convicted of any infamous crime.
--
Keywords: ARMED FORCES